Penentuan Prioritas Komoditas Unggulan Buah-Buahan di Kabupaten Minahasa Utara Provinsi Sulawesi Utara: Aplikasi Analisis LQ dan Daya Tarik-Daya Saing - Mira Yulianti (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
North Minahasa is known as the source of fruits production for North Sulawesi Province and surrounding. However, in its development, North Minahasa district has not determined which fruits that can be a superior products. Thus, the research is performed to determine those, especially local fruits. The method used was exploratory method. Primary data was collected through questionnaire and depth-interviews. The samples were purposively taken, consists of: 5 government officers from the Agricultural Agency of North Minahasa regency and BP4K, 3 village chiefs and 3 businessmen. The analysis used were Location Quotient (LQ) and AttractivenessCompetitiveness Analysis. The result showed that the local commodities which became the top priority for the development were rambutan, papaya, rose apple, mango and duku. The study also suggested that local government were recommended to: (1) develop the new and existing area, and (2) increase human resources, both businessmen and farmer groups, and facilitate partnership between them.